Effect of mindfulness-based stress on cancer-related fatigue in breast cancer patients: a systematic review and meta-analysis - Wang, Xiong; Gao, Lei; Pang, Yuqi; Huang, Ting (Frontiers in Oncology, 2025)
BackgroundCancer-related fatigue (CRF) can seriously affect the quality of life of breast cancer patients. Mindfulness-based stress reduction therapy (MBSR) has been increasingly used in the treatment of breast cancer patients to reduce psychological distress and promote emotional and physical health. This review aims to provide an updated assessment of the role of MBSR in reducing CRF and sleep quality in breast cancer patients.ObjectiveTo evaluate the effect of MBSR on cancer-related fatigue in patients with breast cancer.MethodsComputer search PubMed, Embase, Web of Science, Wanfang and other databases, We were able to search for articles related to CRF from MBSR in breast cancer patients from the establishment of the database to October 2023. Researchers independently screened the literature and extracted information. The meta-analysis was performed using Review Manager Software (version 5.3).ResultsA meta-analysis of 11 studies included showed that MBSR could reduce CRF in breast cancer patients (SMD = -0.86, 95%CI = −1.22 ~ −0.50). Improved sleep quality (MD = -2.54, 95%CI = −3.38 ~ −1.70).ConclusionOur research indicates that MBSR can reduce CRF and improve sleep quality in breast cancer patients. However, due to the moderate and significant heterogeneity in the quality of evidence observed in the included studies, these findings should be interpreted with caution.